Cyberbullying y estratégias de afrontamiento en adolescentes del sur de Brasil (2018)
Cyberbullying is defined as a phenomenon that involves aggressive, intentional and repetitive behaviors, carried out through electronic means, during a given time, and perpetrated by an individual or group against a defenseless victim. Coping strategies are a range of changeable cognitive and behavioral efforts used to cope with internal and external demands appraised by the individual as excessive to their resources. This paper aims to investigate the prevalence of cyberbullying among adolescents of two cities in Rio Grande do Sul (Brazil), and its relationship with coping strategies. 273 adolescent boys and girls (M = 14.91 years; SD = 1.45), living in the State capital and in a countryside town took part in this study. Participants were asked to respond to a socio-demographic questionnaire, as well as to the Revised Cyberbullying Inventory and the Coping Strategies Inventory by Folkman and Lazarus. Results indicated that 58 % of the adolescents were included in at least one category of aggression. In addition, the statistical means for self-control, social support and avoidance coping strategies were significantly higher for the victims compared to the not-involved youth. On the other hand, victims-aggressors scored higher on the confrontation strategies than the not involved ones. The great incidence of cyberbullying is discussed, as well as the prevalence of the abovementioned coping strategies.